Laparoscopic versus open inguinal hernia repair in octogenarians: A follow‐up study. Issue 2 (21st June 2012) - Dallas, Kai B; Froylich, Dvir; Choi, Jacqueline J; Rosa, Jonatan Hernandez; Lo, Christopher; Colon, Modesto J; Telem, Dana A; Divino, Celia M
<x xml:space="preserve">Abstract</x> Aim: The elderly population is the fastest growing demographic in developed countries. It is thus imperative to assess common medical procedures in this age group. Inguinal hernia repair is a commonly carried out operation in the USA with two methods of repair existing – laparoscopic and open. Although the advantages of laparoscopic inguinal hernia repair in the general population have been shown, its role in the elderly has yet to be elucidated. Methods: A retrospective medical record review with prospective follow up of 115 patients aged over 80 years who underwent either open or laparoscopic inguinal hernia repair was carried out. Outcome measures included postoperative pain score, recovery time, chronic pain, wound infection, urinary retention, urinary tract infection, hematoma and recurrence. Patient satisfaction was measured with the Likert score. Results: Of the 115 repairs, 31 repairs were carried out laparoscopically and 84 open. Mean patient age was 83.3 years (range 80–95 years), with no difference in demographics or comorbidities between the two groups. Mean recovery time was significantly shorter in the laparoscopic group (7.5 vs 23.1 days, P = 0.02), as was the mean duration of pain in the laparoscopic group (1.4 vs 9.6 days, P = 0.04). There were no significant differences in other outcomes. There was a trend towards increased patient satisfaction in the laparoscopic group (P = 0.10). Conclusion: In octogenarians, laparoscopic inguinal hernia repair confers a significantly shorter duration of pain and recovery time as compared with open inguinal hernia repair, with no increase in complications. For elderly patients, laparoscopy is a viable alternative to open repair. Geriatr Gerontol Int 2013; 13: 329–333.